Long-term outcome of patients with intermediate- and high-risk endometrial cancer after pelvic and paraaortic lymph node dissection: a comparison of laparoscopic vs. open procedure - Papathemelis, Thomas; Oppermann, Helen; Grafl, Stella; Gerken, Michael; Pauer, Armin; Scharl, Sophia; Scharl, Anton; Inwald, Elisabeth; Ignatov, Atanas; Ortmann, Olaf; Klinkhammer-Schalke, Monika; Hein, Alexander; et al. (Journal of Cancer Research and Clinical Oncology, 2020)
Objective: The primary therapy for intermediate- and high-risk endometrial cancer includes pelvic and paraaortic lymph node evaluation. Laparoscopic surgery is an increasingly popular intervention due to decreased risk and better short-term morbidity; however, a recent study casts doubt on the benefit of this approach in terms of oncological safety. In this cancer registry study, we sought to evaluate the benefit of laparoscopy versus laparotomy and retrospectively compared overall survival, recurrence rates, and recurrence-free survival among patients with intermediate- and high-risk endometrial cancer who underwent either laparoscopic or open surgery. Methods: This observational study included 419 patients who have been treated from 2011 to 2017. We employed Kaplan–Meier method, and univariable and multivariable Cox-regression to compare overall survival, recurrence rates, and recurrence-free survival in 110 patients, who underwent laparoscopic, with 309 patients, who underwent open surgery. To address the confounding bias in this retrospective study, we also performed a propensity score matching (PSM) analysis including 357 patients (laparoscopy: n = 107; open surgery: n = 250). Results: We found a benefit for laparoscopic over open surgery in patients with intermediate- and high-risk endometrial cancer for overall survival in both univariable (p = 0.002; PSM: p = 0.016) and multivariable analyses (p = 0.019; PSM: p = 0.007). In contrast, there was no statistically significant difference between both patient groups regarding the cumulative recurrence rates. A univariable analysis identified a significant benefit for laparoscopy regarding recurrence-free survival (p = 0.003; PSM: p = 0.029) but a multivariable analysis failed to confirm this finding (p = 0.108; PSM: p = 0.118). Conclusions: Our study provides evidence that laparoscopic systematic lymphadenectomy does not present a lower oncological efficacy than open surgery in the treatment of patients with endometrial cancer.
CRIS-Team Scopus Importer:2020-01-10
Keywords: Cancer registry study; Endometrial cancer; Laparoscopy; Laparotomy; Observational study; Overall survival; Pelvic and paraaortic lymphadenectomy